Research on asphalt surface layer performance over service time and establishment of ageing model for in-service bitumen under Norwegian conditions - Xuemei Zhang; Rabbira Garba Saba; Hao Chen; Inge Hoff; Jianan Liu; Fusong Wang (Case Studies in Construction Materials, 2024)
Asphalt surface layer as one of the significant pavement layers is directly withstanding traffic loading and external service conditions, and its performance highly determines the life cycle cost of asphalt pavements. Bitumen ageing is an unavoidable process for asphalt surface layer, and it shortens the service life and increases the risk of distress of asphalt pavements. A large number of studies have been conducted on the consequences of asphalt surface layer ageing under ambient environmental conditions. However, the development of asphalt mixture performance under Norwegian conditions and ageing model for the in-service bitumen have not been extensively investigated. Therefore, this work aims to investigate asphalt surface layer performance over service time and establish ageing model for the in-service bitumen. To achieve this goal, core samples acquired from the field and bitumen extracted from in-service field cores were analysed by comparing them with reference bitumen and asphalt mixtures. The physical, chemical, viscoelastic and performance grade variables of the bitumen were characterised, as well as the dynamic modulus and density of asphalt mixtures. The ageing models for bitumen property parameters were established using bitumen type, service time and average annual temperature as independent variables after statistical data processing. As a result, a good agreement between predicted values and measured values of property parameters was achieved because of the high accuracy of prediction of the ageing model. The proposed ageing model for bitumen under Norwegian conditions is beneficial for predicting bitumen properties at specific service time.